Rank-one perturbation bounds for singular values of arbitrary matrices - Lei Zhu; Xiaofei Peng; Hao Liu (Journal of Inequalities and Applications, 2019)
Abstract Rank-one perturbation of arbitrary matrices has many practical applications. In this paper, based on the relationship between the singular values and the eigenvalues, we discuss singular value variations and present two-side bounds of the singular values for rank-one perturbation of arbitrary matrices. Numerical results confirm that the proposed perturbation bounds are sharper than some existing bounds.